Adriamycin Nephropathy in BALB/c Mice. (2nd February 2015) - Wang, Yuan Min; Wang, Yiping; Harris, David C. H.; Alexander, Stephen I.; Lee, Vincent W. S.
Abstract: Chronic proteinuric renal injury is a major cause of end stage renal disease. Adriamycin nephropathy (AN) is a murine model of chronic proteinuric renal disease whereby chemical injury is followed by immune and structural changes that mimic human disease. This unit describes the method of AN induced by a single injection of adriamycin (ADR) in BALB/c mice. After the initial toxic injury, an immune‐mediated chronic proteinuric renal disease that resembles human focal segmental glomerulosclerosis develops. The clinic pathological features of AN are nephrotic syndrome, focal glomerulosclerosis, tubular injury, and interstitial compartment expansion with mononuclear cell infiltrates that are composed largely of macrophages and T cells. © 2015 by John Wiley & Sons, Inc.